2000
DOI: 10.1038/sj.bmt.1702464
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of allogeneic peripheral blood mononuclear cells mobilized with granulocyte-colony stimulating factor

Abstract: Summary:The use of mobilized peripheral blood (PB) stem cells for autologous transplantation initially generated much enthusiasm because of enhanced engraftment in comparison to marrow stem cells and avoidance of general anesthesia for the donor. Its application to the allogeneic setting seemed inevitable. For obvious ethical reasons, allogeneic donors are mobilized with cytokines only, mainly granulocyte colony-stimulating factor (G-CSF).Results from preliminary studies suggest that in comparison to standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 195 publications
(126 reference statements)
0
20
0
1
Order By: Relevance
“…[19][20][21][22][23]25 While results vary between studies, the influence of rhG-CSF has been reported on monocytes, 21 T cells [21][22][23] and NK cells. 20,22,23 There are contradictory reports on changes in the absolute numbers of NK cells and their proportion within total lymphocytes, following rhG-CSF administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23]25 While results vary between studies, the influence of rhG-CSF has been reported on monocytes, 21 T cells [21][22][23] and NK cells. 20,22,23 There are contradictory reports on changes in the absolute numbers of NK cells and their proportion within total lymphocytes, following rhG-CSF administration.…”
Section: Discussionmentioning
confidence: 99%
“…18 In this context, it is important to determine what are the consequences on lymphocyte populations of the use of pharmacological doses of rhG-CSF to mobilise haematopoietic progenitors in donors. Most published reports [19][20][21][22][23][24] have focused on T-cell phenotype or function, and suggest that rhG-CSF may truly be an immunomodulator in addition to being a mobilisation agent. Manipulation of the NK cell compartment will require an assessment of the consequences of rhG-CSF exposure on this cell population.…”
mentioning
confidence: 99%
“…Awareness of the association between HBV reactivation and cGVHD is especially relevant when one considers that cGVHD occurs in the majority of patients receiving HLA non-identical-related transplants, matched unrelated transplants, and HLA matched mobilized peripheral blood allogeneic stem cell transplants. 44,45 As suggested by Strasser and McDonald, 46 these patients should be monitored for HBV DNA from 2 weeks post transplant. Early initiation of pre-emptive antiviral therapy upon obtaining positive results may abrogate HBV replication during the window of post-transplant defective thymopoiesis and limit CTL-induced hepatocellular damage at the critical time of immune recovery and immunosuppressive therapy withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF is being used to reconstitute the hematopoietic system of cancer patients after chemotherapy or radiation therapy, whereas erythropoietin and thrombopoietin are being used for the treatment of anemia and thrombocytopenia, respectively (4,5).…”
Section: Cd137 Induces Proliferation Of Murine Hematopoietic Progenitmentioning
confidence: 99%